An interleukin 12 p40-IgG2b fusion protein abrogates T cell mediated inflammation: anti-inflammatory activity in Crohn's disease and experimental colitis in vivo. (11th February 2004) - Stallmach, A; Marth, T; Weiß, B; Wittig, B M; Hombach, A; Schmidt, C; Neurath, M; Zeitz, M; Zeuzem, S; Abken, H
Abstract : Background and aims: Interleukin-12 (IL-12), a p35/p40 heterodimer, plays a pivotal role in the immune response in Crohn's disease (CD). Since IL-12 p40 dimers act as IL-12 antagonists, we assayed p40 dimer proteins to modulate chronic intestinal inflammation. Methods: We generated a fusion protein consisting of the IL-12(p40) subunit fused to the constant region of IgG2b. IL-12(p40)-IgG2b was tested in a murine 2, 4, 6, -trinitrobenzene sulphonic acid (TNBS) colitis model and in lamina propria mononuclear cells (LPMNC) from patients with CD in vitro. Results: Dimeric IL-12(p40)-IgG2b fusion protein bound specifically to the IL-12 receptor. In concentrations <10 −7 M, it acted as an IL-12 antagonist as it inhibited interferon γ (IFN-γ) secretion, suppressed proliferation, and increased apoptosis of LPMNC from patients with CD. However, in concentrations >10 −6 M, IL-12(p40)-IgG2b increased IFN-γ secretion and lymphocyte proliferation thereby acting as an IL-12 agonist. In TNBS colitic mice, IL-12(p40)-IgG2b decreased mortality (10% v 68%), prevented body weight loss, reduced tumour necrosis factor α, and increased IL-10 secretion. Conclusions: The IL-12(p40)-IgG2b fusion protein has dichotomic properties as a specific IL-12 antagonist and selective repressor of mucosal inflammation at low concentration and as an IL-12 agonist at high concentration.